THE INFLUENCE OF THE USE OF PICTORIAL MODULE ON THE SUBJECT OF FORCE TO THE STUDENTS LEARNING RESULT IN PHYSICS EDUCATION DEPARTMENT - Safitri, Baiq Rina Amalia (IKIP Mataram, 2017)
This study aims to improve student physics education learning outcomes in computational physics courses by using a valid and practical drawing module. In the first stage, students are assigned to read and understand the style material contained in the pictorial module. To ensure they read and understand the material, the next session is a quiz. Quiz done through writing. For students who can not answer are given remedial until they can be sure read the existing teaching materials. In the second stage, students are considered to have sufficient stock in understanding the reading material, the students at this stage are no longer assigned to read and understand the material but to practice the material, such as calculating the style. The result of the practice of the students in the first stage, reading and understanding the material contained in the pictorial module, as many as 82.35% or 14 students passed the practice without having to remedial, while the rest as much as 17.65% or 3 new people declared passed after remidial. In the second stage, students are assigned to practice style materials on the pictorial module, 100% complete achievement.